Clinical Outcome in Human T-Lymphotropic Virus Type 2 Carriers Following Organ Transplantation - Benito, Rafael; Gil, Joaquina; Sahagún, Juan; Soriano, Vicente (Transplantation proceedings, 2021)
Background Frequent and rapid development of myelopathy has been reported in individuals with human T-lymphotropic virus type 1 (HTLV-1) infection following solid organ transplantation. There is no information regarding HTLV-2, a closely related virus that often infects injection drug users. Methods This study includes a retrospective analysis of all consecutive organ transplants performed during the last 2 decades at a large reference transplantation unit in Spain. All participants were tested for anti-HTLV antibodies. Results A total of 2019 individuals were tested for HTLV during the study period, including 663 potential donors and 1356 recipient candidates. Twelve (0.59%) were reactive on initial HTLV serologic screening, but only 6 (all recipients) were confirmed as positive, all for HTLV-2. Two recipients underwent liver transplantation and have remained asymptomatic despite being on tacrolimus for 4 and 8 years, respectively. Likewise, the remaining 4 HTLV-2 carriers have not developed clinical complications potentially associated with HTLV-2. Conclusions Unlike HTLV-1 infection, HTLV-2 infection in the transplantation setting does not seem to be associated with rapid development of neurologic complications, Given the cross-seroreactivity between HTLV-1 and HTLV-2, discriminatory rapid tests are urgently needed and would reduce unnecessary organ discharge.
Keywords: human T-Lymphotropic virus type 2; organ transplantation; Scopus; WOS(2)